Enhancing the Social Amplification of Risk Framework (SARF) by exploring trust, the availability heuristic, and agricultural advisors' belief in climate change. (March 2015) - Mase, Amber S.; Cho, Hyunyi; Prokopy, Linda S.
Abstract: Using a survey of agricultural advisors across the Midwestern U.S., this paper explores two additions to the Social Amplification of Risk Framework (SARF)—trust in information sources and the availability heuristic. Connections between demographic factors, belief in climate change, perceived risk, and advisors' attitudes toward adaptation to climate change are examined. Three-fourths of advisors believe climate change is occurring, but disagree on the human contribution. Trust in information sources predicted agricultural advisors' belief in climate change. Consistent with the availability heuristic, perceiving variability in weather made advisors more likely to believe in anthropogenic climate change. Believing climate change is at least partly human caused increased agreement that agricultural adaptation is important. Perceiving greater risk from potential climate impacts and noticing variable weather also significantly increased adaptation attitudes. Findings suggest that trust and availability heuristic could be added to help explain the processes of social amplification and attenuation of risk. Highlights: Advisors' climate change beliefs vary based on area of specialization and gender. Trust in information sources is positively correlated with climate change belief. Belief in climate change is positively correlated with concern with weather risks. The availability heuristic and trust explain adaptation attitudes within the SARF.